Penerapan Lembar Kerja Siswa dan Puzzle Untuk Meningkatkan Prestasi Belajar Trigonometri Pada Siswa X TKI 1 SMK Negeri 5 Malang - Dwi Paraningsih (Warta Pendidikan | e-Journal, 2020)
The objective of this research is to describe the impact of use of Student Worksheets and Puzzle in learning the material of Trigonometry in grade X SMKN 5 Malang. The research method is classroom action research. The subject of this reseach are 37 students of class X TKI 1 at SMK Negeri 5 Malang . This reseach can increase the academic achievement that can be seen by comparing the results of learning in cycle 1 and cycle 2. The test and observation sheets (teachers and student’s activity) are the instruments which were used. Based on the results of reseach suggest that 85% of students have scored ≥ 75. Worksheet results indicate that students are able to understand the concept of trigonometry itself. The puzzle makes students feel refreshing and practice lots of exercises. It can be concluded that the use of Student Worksheets and Puzzle can understand the concepts and improve student’s learning outcomes in the material of trigonometry in SMKN 5 Malang.